Web GIS to enhance relational capital: the case of general merchandise retailers. Issue 3 (9th May 2016) - Baños, Raul; Wandosell, Gonzalo; Parra, María Concepción
Abstract : Purpose: This paper aims to study the impact of information and communication technologies in organizations to capture and manage intellectual capital. The paper focuses particularly on the use of Web-based geographical information systems (Web GIS) to increase relational capital. Design/methodology/approach: This paper analyzes in detail the Web sites of 143 general merchandise retailers, which have been grouped according to their dominant operational format. Menus and search tools have been used to find out about the way in which these retailers provide information to the customers about their stores, with special attention to the use of Web GIS. Findings: The results obtained show that most of the companies analyzed use Web GIS to provide information about the location and other characteristics of the stores. The findings in this paper also suggest that the quantity and quality of the information provided by is somewhat related to the company size. Research limitations/implications: The limitations of this study come from the difficulty of predicting whether small and medium enterprises (SMEs) will generalize the use of Web GIS in the future. Practical implications: The findings of the paper suggest that large retail firms have adopted Web GIS to provide information to the customers and for other geomarketing purposes. Moreover, SMEs should use Web GIS to improve their relationship with customers. Originality/value: To the authors' knowledge, no paper has analyzed in detail the use of Web GIS by companies with the aim of enhancing relational capital.